2015
DOI: 10.5194/soil-1-235-2015
|View full text |Cite
|
Sign up to set email alerts
|

The soil N cycle: new insights and key challenges

Abstract: Abstract. The study of soil N cycling processes has been, is, and will be at the centre of attention in soil science research. The importance of N as a nutrient for all biota; the ever-increasing rates of its anthropogenic input in terrestrial (agro)ecosystems; its resultant losses to the environment; and the complexity of the biological, physical, and chemical factors that regulate N cycling processes all contribute to the necessity of further understanding, measuring, and altering the soil N cycle. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(102 citation statements)
references
References 231 publications
(233 reference statements)
0
99
0
3
Order By: Relevance
“…Sanford et al (2012) suggested that nondenitrifying populations with a broad range of metabolisms and habitats are potentially significant contributors to N 2 O consumption, therefore controlling N 2 O emissions. However, the mechanisms and controls of N 2 O consumption in soil are not clear, and various biochemical routes have been identified in addition to the classical reduction of N 2 O during denitrification (van Groenigen et al 2015); these routes include dissimilative reduction, a direct assimilatory N 2 O fixation via nitrogenase (Vieten et al 2008;Farías et al 2013). Recently, Wu et al (2013) reported a significant N 2 O consumption occurring under aerobic conditions, with a rising N 2 O consumption with increased soil moisture content, and the complete blockage of N 2 O consumption with the sterilization of oxic soil.…”
Section: Discussion Environmental Conditions In the Reloncaví Estuarymentioning
confidence: 99%
“…Sanford et al (2012) suggested that nondenitrifying populations with a broad range of metabolisms and habitats are potentially significant contributors to N 2 O consumption, therefore controlling N 2 O emissions. However, the mechanisms and controls of N 2 O consumption in soil are not clear, and various biochemical routes have been identified in addition to the classical reduction of N 2 O during denitrification (van Groenigen et al 2015); these routes include dissimilative reduction, a direct assimilatory N 2 O fixation via nitrogenase (Vieten et al 2008;Farías et al 2013). Recently, Wu et al (2013) reported a significant N 2 O consumption occurring under aerobic conditions, with a rising N 2 O consumption with increased soil moisture content, and the complete blockage of N 2 O consumption with the sterilization of oxic soil.…”
Section: Discussion Environmental Conditions In the Reloncaví Estuarymentioning
confidence: 99%
“…Although the use of nitrogen fertilizers contributes to the increase in pasture production (Boddey et al, 2000;Palmer et al, 2014), their use have limited efficacy because of the complex steps in the nitrogen cycle which occurs in the soil, and which can result in the loss of the fertilizer after its application (Van Groenigen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soils are self-organized heterogeneous porous media essential for supporting life within the Earth system, as they control the hydrological and biogeochemical cycles, among other biospherical services (Keesstra et al, 2012;Billings et al, 2015;Brevik et al, 2015b;de Graaff et al, 2015;Köchy et al, 2015;van Groenigen et al, 2015). The Iberian Peninsula has a long history of soil use.…”
Section: Introductionmentioning
confidence: 99%